Happy sands - Howard, Barb, 1962- (Brave & brilliant series, 2021)
"Ginny, a jaded massage therapist with an eye for body details, sets off with her husband Martin and their two kids Alistair and Ruby for their annual summer vacation at Happy Sands Resort. The cast of returning renters at the resort includes two power-boating families, a cranky mom with her Goth daughter, an elderly couple, a devilish set of twins, and, oh, new this year at the resort - Dwayne the Uberman. Through her inner commentary we learn about the bodies and the dynamics of the renters, and we learn that Ginny rarely speaks her mind. Through the actions of the characters we learn that even Ginny's inner commentary may not be entirely reliable. The Albertans water ski, Mrs. Edwards stands by her pink flamingoes, Ginny tries to get massage work and drinks too much, Martin is depressed. Dwayne, buff and tri-fit, and alpha, stirs up the mix and stirs up Ginny. What's with him? And why is he so goddam happy? And why does he smell like mint? Through the course of the story Ginny's kids leave her for other kids/families, a group bonfire is a serious social flop, the flamingoes disappear and, after Dwayne dies on the massage table, Martin steps up and Ginny begins to speak her mind - foul and irreverent as it is. Conceived initially as a Western Canadian "summer read", Happy Sands offers up plenty of water, barbecue, boats, and short-shorts, but is also multilayered enough to allow for a re-read in the dark of winter and some delving into the meaning of the story's mythical fish: Big Red."--